The Rising Burden of Salmonellosis Caused by Monophasic Salmonella Typhimurium (1,4,[5],12:i:-) in Greece and New Food Vehicles - Georgia Mandilara; Theologia Sideroglou; Anthi Chrysostomou; Iliodoros Rentifis; Theofilos Papadopoulos; Michalis Polemis; Myrsini Tzani; Kyriaki Tryfinopoulou; Kassiani Mellou (Antibiotics, 2021)
Monophasic Salmonella typhimurium is of increasing importance worldwide. Here we present the available data regarding monophasic S. typhimurium from 2007 to 2019 in Greece, in order to assess its public health impact. Surveillance data, data on antimicrobial resistance, molecular typing by pulsed-field gel electrophoresis (PFGE), and results of the investigation of monophasic S. typhimurium outbreaks were analyzed. Overall, 403 cases were identified; 329 (81.6%) sporadic and 74 (18.4%) related to two community outbreaks in 2017. A total of 305 isolates from sporadic cases tested for antimicrobial resistance revealed resistance to ampicillin, streptomycin, sulphamethoxazole, and tetracycline (41.3%). Some 23.3% were further resistant to trimethoprim and 5.2% were also resistant to chloramphenicol. Outbreak 1 in 2017 with 37 identified cases was attributed to the consumption of raw milk from a vending machine and isolates were resistant to ampicillin, streptomycin, sulphamethoxazole, tetracycline, and trimethoprim. Outbreak 2 also with 37 cases was attributed to the consumption of pork and isolates were resistant to the five above mentioned antibiotics plus chloramphenicol. The number of human monophasic S. typhimurium isolates is low; however, since 2009, it has been among the five most frequently identified serotypes in Greece. Investigation of the outbreaks revealed that other vehicles apart from pork may be implicated in the occurrence of outbreaks.